INVESTIGATING VOCABULARY ACQUISITION OF SECOND SEMESTER STUDENTS OF ENGLISH DEPARTMENT - Dimas Saiyidati Munawaroh (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: Learning English is very important in this modern era. In learning English, there is an important part that is the main key to understand language, namely vocabulary. Vocabulary is the basis of a language, therefore learning vocabulary is very important, because the language will not have meaning without vocabulary. This research examines how the second semester students of English Education Department Unisma obtain vocabulary to get a high score in reading. The instruments used to collect the data was semi-structured interview.The researcher asked questions via WhatsApp and the participants answered them via voice note. After conducting interviews with the participants, the data were transcribed and arranged into written form. Then, the results were arranged into a description.The finding of this research showed thatthe students improved their vocabularies by watching movies using English subtitles, reading online, reading articles, listening music, and using dictionaries. Based on the finding of the study,vocabulary acquisition can be obtained by the habit of carrying out activities such as reading text,listening music,watching movies using English subtitles.Key words: Language Acquisition, Vocabulary, Vocabulary Acquisition